In silico analysis of free heme action on the dimerization and activity of the human redox sensor PARK7 - Barannik, T.; Karabtsova, N. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2025)
Protein PARK7 (Parkinson disease protein 7) has several enzymatic activities and also functions as a redox sensor,copper chaperone andtranscription regulator. Under oxidative stress PARK7promotes cell survival by activating the ERK1/2 and the PIK3 signaling. PARK7 inactivation causes the reactive oxygen species accumulation and oxidative stress progression. PARK7 disorders has been revealed under neurodegenerative diseases, diabetes and other pathologies. PARK7 functioning is based on the redox changes of conserved Cys106 in the active center. In some neurodegenerative diseases, such as Parkinson's disease, the superoxidation of redox-activeCys106is the basis of the disorder. The removal of 15 amino acid residues from C-end is an obligatory step for the proteolytic active center formation. Modifications observed under oxidative stress affect dimerization of PARK7 necessary for protein maximum activation.Erythrocyte lysis is known to result in a significant heme accumulation but heme effect on the activity of PARK7 has not yet been investigated. Therefore, the potential heme-binding sites in PARK7 and heme binding effect on the amino acid residues were analyzed.Structural alignment of PARK7 mutant forms with Cys53 and Cys106 substitutions and wild type has not revealed significant differences (RMSD<0.2Å). Two areas have been found as probable targets for heme binding in PARK7: near the C-terminal region (175-189) that is cleaved for protein activation and in the redox-center with Cys106 and His126. Heme binding to the PARK7 protein could potentially affect its activity by several mechanisms. C-end heme binding can prevent peptide removal necessary for catalytic activity. Cys106 oxidative modification to sulfinic acid could occur under low free heme level and activate PARK7 as a cytoprotector. Significant heme accumulation can result in cysteine superoxidation to sulfonic acid and disrupt PARK7 functionality. Free iron ions as products of heme degradation can compete with copper ions for Cys106 and Glu18 residues therefore inhibit PARK7 activity as SOD1 chaperon. Heme attachment to the sites of oxidation (Cys46, 53 and 106) or sumoylation (Lys130) could disrupt the regulation of PARK7 under stress. Some of the potential heme binding sites of PARK7 protein are involved in protein dimerization, so hemecan block the formation of functional PARK7 dimers.Therefore free heme accumulation could have multiple negative effect on PARK7 functioning and be one of the mechanisms of PARK7-dependent neurological disorders.